EAEU’s Human Potential: New Risks and Opportunities for Development - N. V. Yurova (Евразийская интеграция: экономика, право, политика)
This study is aimed at studying human potential, its development and implementation in the Eurasian Economic Union (EAEU). Taking into account the commitments made by the countries of the Union to achieve the Sustainable Development Goals (SDGs) in accordance with Agenda 2030 and under sanctions pressure from hostile countries.Aim. To present the human potential of the integration association as a complex phenomenon of the socio-economic relations of the integrating countries, as well as to identify the emerging risks and offer practical recommendations for reproducing the human potential within the EAEU.Tasks. To trace the dynamics of indicators of development and realization of human potential in each country of the EAEU and the aggregate human potential of the EAEU, to reveal the features of reproduction of human potential by dividing it into qualitative and functional forms, to identify modern risks for reproduction of human potential of the EAEU and new opportunities for development.Methods. To compare indicators of human development of the EAEU countries, the method of comparative analysis is used. In the part of the human potential of the EAEU, it is proposed to take into account new risks for ensuring sustainable human development in the integration association, which make it possible to make methods of analysis and synthesis, induction and statistical method.Results. Based on the analysis of the dynamics of development of such forms of human potential as health potential, educational potential and labor potential, accumulated problems, modern challenges and risks for reproduction of human potential of each EAEU country.Conclusion. The EAEU can no longer remain only an economic integration project, and it is time to expand the horizons of interaction between countries, including on the sphere of development and the realization of human potential. By taking into account new risks, countries need to coordinate the directions of development of the EAEU’s total human potential within the framework of commitments to achieve the Sustainable Development Goals in accordance with Agenda 2030 and under the conditions of ongoing sanctions pressure from hostile countries.